1980
DOI: 10.1037/0022-006x.48.6.685
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunctional cognitions and the effectiveness of skills and cognitive behavioral assertion training.

Abstract: Dysfunctional cognitions have been hypothesized to be important determinants of unassertive responding, although treatment strategies aimed directly at modifying cognitions have generally proved no more effective than skills training interventions alone. However, the possibility that individual differences in dysfunctional cognitions may interact with type of treatment has not been previously explored. Nonstudent adults with assertion problems and with high or low levels of dysfunctional attitudes were assigne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
1

Year Published

1982
1982
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(19 citation statements)
references
References 19 publications
2
16
0
1
Order By: Relevance
“…Consistent with findings from Linehan et al (1979), results revealed that cognitive restructuring and behavioral rehearsal were equally effective in improving selfreported assertiveness and reducing fear of negative evaluation (Hammen, Jacobs, Mayol, & Cochran, 1980). Consistent with findings from Linehan et al (1979), results revealed that cognitive restructuring and behavioral rehearsal were equally effective in improving selfreported assertiveness and reducing fear of negative evaluation (Hammen, Jacobs, Mayol, & Cochran, 1980).…”
Section: Treatment Outcomesupporting
confidence: 78%
See 2 more Smart Citations
“…Consistent with findings from Linehan et al (1979), results revealed that cognitive restructuring and behavioral rehearsal were equally effective in improving selfreported assertiveness and reducing fear of negative evaluation (Hammen, Jacobs, Mayol, & Cochran, 1980). Consistent with findings from Linehan et al (1979), results revealed that cognitive restructuring and behavioral rehearsal were equally effective in improving selfreported assertiveness and reducing fear of negative evaluation (Hammen, Jacobs, Mayol, & Cochran, 1980).…”
Section: Treatment Outcomesupporting
confidence: 78%
“…Treatment outcome studies have found that assertiveness training improves general self-esteem, self-concept, and internal locus of control (Hammen et al, 1980;Meyer, 1991;Percell et al, 1974;Warren, 1977;Workman et al, 1986). Treatment outcome studies have found that assertiveness training improves general self-esteem, self-concept, and internal locus of control (Hammen et al, 1980;Meyer, 1991;Percell et al, 1974;Warren, 1977;Workman et al, 1986).…”
Section: Self-esteemmentioning
confidence: 99%
See 1 more Smart Citation
“…Loeffler and Fiedler (19791 found that assertiveness training and cognitive restructuring along with other interventions helped women to become more confident, competent, less anxious, and freer. An assertiveness program that includes skill acquisition, modification of cognitive processes, and changes in underlying beliefs about the world has been advocated by Hammen, Jacobs, Mayol, and Cochran (1980). Worell (1980) advocated multiple skill development, which included training in assertiveness skills and negotiation skills, to help increase com-petence and productivity.…”
Section: Confronting External Barriers Throughmentioning
confidence: 99%
“…Wolfe & Fodor, 1977 απέτυχαν να δείξουν ποια από τις παραπάνω αιτίες είναι κυρίαρχη. Κάποιες άλλες έρευνες απέτυχαν να δείξουν αν κάποιο στοιχείο της προσωπικότητας συνδέεται άμεσα με την έλλειψη διεκδικητικότητας (Hammen, Jacobs, Mayol, & Cochran, 1980. Valerio & Stone, 1982.…”
Section: κεφαλαιο 1 διεκδικητικοτηταunclassified